Peran Digital Mareting dan Branding Produk dalam Pengembangan UMKM di Kelurahan Karangtengah - Anita Wulandari; Ikfina Rosyada Kamila; Rizkiyatul Awwalu Bil Khikmah; Bahtiar Arifuddin Fadturahman; Gerry Mario Alexis Martua Manalu; Dewi Puspa Arum (Jurnal Pengabdian Masyarakat Waradin, 2023)
In today’s modern era, the development of small and medium-sized enterprises (SMEs) must be able to innovate in order to attract the attention of consumers and maintain their efforts. Many UMKMs experienced a decline in sales and could not grow even bankrupt during the Covid-19 pandemic last year. These conditions make the UMKM perpetrators have to think to be able to survive for the sake of their efforts. The transition of offline shopping to online (digitalized) in modern times will make it easier for UMKM to expand marketing access. The role of digital technology has a significant impact on UMKM. Emerging technological paradigms leverage the potential of a stronger and more sustainable UMKM. Social media and e-commerce can be the sales container of UMKM offenders. The aim of the community empowerment program on UMKM in the Middle East is to provide support for digital marketing training as an effort to develop and expand the technology-based marketing network (digital). After doing this dedication, it is hoped that the UMKM perpetrators in the Middle Coral Coral will continue to synergize for the sustainability of UMKM and the development of the economy of the community.